The Role of the Ecosystem Engineer, the Leaf-Cutter Ant Atta cephalotes, on Soil CO2 Dynamics in a Wet Tropical Rainforest - Fernandez Bou, Angel Santiago (2019)
Leaf‐cutter ants are dominant herbivores that disturb the soil and create biogeochemical hot spots. We studied how leaf‐cutter ant Atta cephalotes impacts soil CO2 dynamics in a wet Neotropical forest. We measured soil CO2 concentration monthly over 2.5 years at multiple depths in nonnest and nest soils (some of which were abandoned during the study) and assessed CO2 production. We also measured nest and nonnest soil efflux, nest vent efflux, and vent concentration. Nest soils exhibited lower CO2 accumulation than nonnest soils for the same precipitation amounts. During wet periods, soil CO2 concentrations increased across all depths, but were significantly less in nest than in nonnest soils. Differences were nonsignificant during drier periods. Surface efflux was equal across nest and nonnest plots (5 μmol CO2 m−2 s−1), while vent efflux was substantially (103 to 105 times) greater, a finding attributed to free convection and sporadic forced convection. Vent CO2 concentrations were less than in soil, suggesting CO2 efflux from the soil matrix into the nest. Legacy effects in abandoned nests were still observable after more than two years. These findings indicate that leaf‐cutter ant nests provide alternative transport pathways to soil CO2 that increase total emissions and decrease soil CO2 concentrations, and have a lasting impact. Estimated total nest‐soil CO2 emissions were 15 to 60% more than in nonnest soils, contributing 0.2 to 0.7% to ecosystem‐scale soil emissions. The observed CO2 dynamics illuminate the significant carbon footprint of ecosystem engineer Atta cephalotes and have biogeochemical implications for rainforest ecosystems.